Incest Taboos in Sacred Texts: Theological and Historical Analysis of Prohibitions and Sanctions in Abrahamic Religions - Rahimah; Taufik Wal Hidayat; Lila Pelita Hati (Pharos Journal of Theology)
The study examines the role of religion in shaping and enforcing social norms regarding the taboo of incest, with a focus on theological and historical interpretations within Judaism, Christianity, and Islam. Incest, as a form of intrafamilial sexual violence, is under-researched due to societal stigma. The research aims to provide insights into how religion influences values and social order, especially concerning taboo subjects like incest. A qualitative phenomenological approach is used, gathering primary data through interviews with religious leaders, academics, and individuals with personal experiences, alongside secondary data from sacred texts and academic sources. The findings reveal that the prohibition of incest in Abrahamic religions serves as both a moral rule and a social regulatory tool, reinforcing family and societal boundaries. The sacred texts from these religions explicitly forbid incest, with corresponding sanctions, underscoring the sanctity of family. The study also explores how these religious interpretations shift in response to social and cultural changes. This research offers a new perspective on the relationship between theology, law, and social structures, emphasizing religion's proactive role in addressing taboo issues, including offering solutions grounded in theological principles. It calls for a more open, inclusive approach to research on neglected and sensitive issues like incest.